Hubungan Antara Efektivitas Tim Dengan Stress Pada Karyawan Unit Frontline Bank “X” Cabang Jpk Bandung - Ali Mubarak; Miki Amrilya (Universitas Islam Bandung, 2011)
PT Bank X Persero (Tbk) a company's profit in banking services that focus on services that are consideredimportant in the Success of the company. The unit is responsible for achieving success in providing these services the frontline units. Competence of each employee’s frontline units of course is needed in the process Of achievement. Frontline employees to work as a team unit In the completion of tasks and responsibilities for the achievement of corporate goals is to serve customers with the best – good. The success of frontline units as a team In achieving the goals can not only rely on the capabilities of human resources. but the psychological condition should be good. At Bank X Branch Road Independence Pioneer frontline units indicates a condition that not an effective team. Frontline units consisting of the teller and customer service would require the existence of effective teamwork to achieve common goals Teams that are not effective condition occurs along with the same Symptoms –certain symptoms that describe the condition of stress on employees frontline units PT Bank